2002
DOI: 10.1542/peds.109.4.e56
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Consequences of an Overlap of Breastfeeding and Pregnancy: Reduced Breast Milk Intake and Growth During Early Infancy

Abstract: ABSTRACT. Objective. Despite cultural pressure to wean when a new pregnancy occurs, some women choose to continue breastfeeding. We determined the effect of an overlap of lactation and late pregnancy on breastfeeding and growth in early infancy.Methods. We studied 133 Peruvian pregnant women who were >18 years of age, had a child <4 years old, and who then had a vaginal birth with a healthy, normal weight infant. Of the 133 women, 68 breastfed during the last trimester of pregnancy (BFP), and 65 had not breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 26 publications
2
32
0
6
Order By: Relevance
“…Guy et al (1994) demonstrated that prepartum milking of udder halves resulted in less concentration of IgG 1 in secretions of milked glands than in dry glands from 10 days prepartum to 1 day postpartum. Similarly, an overlap of breast feeding and late pregnancy in humans was accompanied by reduced concentration of IgG in colostrum (Marquis et al, 2002). We showed that CM reduces the IgG content of colostrum compared with cows given 30-day dry period in primiparous cows, but it had no effect on colostrum IgG content in multiparous cows (Annen et al, 2004a, Collier et al, 2004.…”
Section: Altered Dry Periodsmentioning
confidence: 50%
“…Guy et al (1994) demonstrated that prepartum milking of udder halves resulted in less concentration of IgG 1 in secretions of milked glands than in dry glands from 10 days prepartum to 1 day postpartum. Similarly, an overlap of breast feeding and late pregnancy in humans was accompanied by reduced concentration of IgG in colostrum (Marquis et al, 2002). We showed that CM reduces the IgG content of colostrum compared with cows given 30-day dry period in primiparous cows, but it had no effect on colostrum IgG content in multiparous cows (Annen et al, 2004a, Collier et al, 2004.…”
Section: Altered Dry Periodsmentioning
confidence: 50%
“…Breastfeeding while being pregnant is associated with different feeding practices than breastfeeding only (eg tending to provide other liquids more frequently), and with a higher proportion of infants receiving low amounts of breast milk (Marquis & Penny, 2000). The composition of colostrum may also differ (eg lower lactoferrin and higher lysozyme concentration in milk from overlapping mothers; Marquis et al, 2002).…”
Section: Changes In Mns During Overlap Between Lactation and Next Prementioning
confidence: 99%
“…Bu da bize birlikte emzirmenin yenidoğanın alacağı süt miktarını etkilemediğini düşündürmektedir. Bu çalışmanın sonucunda da yazarlar daha uzun süren bir kohort çalışmaya ihtiyaç olduğunu belirtmişlerdir (14). Moscone ve Moore'un retrospektif olarak yaptığı anket araştırmasında, çalışmaya katılan elli yedi anneden iki tanesi ilk üç ayda , bir tanesi de son üç ayda hamilelik ve sonraki dönemde yorulduğu için emzirmeyi bıraktığını bildirmiştir (10).…”
Section: Discussionunclassified